2019
DOI: 10.1038/s41598-019-52575-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and diagnostic marker for TTG1 regulating tannin and anthocyanin biosynthesis in faba bean

Abstract: Condensed tannins, found in coloured-flowering varieties of faba bean (Vicia faba L) are, after vicine and convicine, one of the major anti-nutritional factors for monogastric animals. The development of tannin-free cultivars is a key goal in breeding to broaden the use of this legume in the animal feed industry. Two recessive genes, zt-1 and zt-2, control the zero-tannin content and promote white-flowered plants. Previous studies exploiting synteny with the model Medicago truncatula reported a mutation in TTG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 42 publications
2
37
0
1
Order By: Relevance
“…Previous studies ascribed this locus to the distal part of chr. III 26,28,29 . The last authors also reported a KASP marker (SNP marker Vf_Mt7g100500_001), 10.5 cM far from flower colour, as a successful marker to discriminate low tannin plants although the closest flanking marker (Vf_Mt1g072740_001), 3 cM apart, failed to distinguish contrasted genotypes in the validation panel 29 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies ascribed this locus to the distal part of chr. III 26,28,29 . The last authors also reported a KASP marker (SNP marker Vf_Mt7g100500_001), 10.5 cM far from flower colour, as a successful marker to discriminate low tannin plants although the closest flanking marker (Vf_Mt1g072740_001), 3 cM apart, failed to distinguish contrasted genotypes in the validation panel 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The approach ascribed the target zt2 region in the distal part of faba bean chr. III between the ESTs markers Pis-Gen-8-1-1 and LG38 26,28 . Using the sequence information deposited in the M. truncatula Genome Database (MTGD) (http://www.medicagogenome.org/), these genes corresponded to…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations